OPTIMASI BIODIESEL DENGAN PREKUSOR MINYAK KELAPA - Paendong, Jessy; Tangkuman, Herling D. (CHEMISTRY PROGRESS, 2019)
Biodiesel more advantages than fuel from diesel and earth oil. Besides that, biodiesel can be renewable. Theobjective of this research was to study the characteristic of biodiesel from coconut oil. The result shows thatethanol (85%) and methanol (87%) were suitable to obtain biodiesel. Optimum volume to obtain biodiesel was30%, the optimum esterification time was 30 minutes to 50 minutes, the best bases used in optimation wereNaOH and KOH, pH 6, flash poin was 104, and viscosity was 2,7. Coconut oil is good as a precursor ofbiodiesel.